Genetic improvement of farmed animals - Simm, Geoff; Pollott, Geoff; Mrode, Raphael A.; Houston, Ross; Marshall, Karen (CAB International, 2020)
Genetic Improvement of Farmed Animals provides a thorough grounding in the basic sciences underpinning farmed animal breeding. Relating science to practical application, it covers all the major farmed animal species: cattle, sheep, goats, poultry, pigs and aquaculture species. The book: - Provides comprehensive coverage - from fundamental genetics, analysis of variation, prediction of breeding values and response to selection, through to application of modern genomics and biotechnology. - Illustrates the practical application of theory in temperate and tropical systems. - Outlines current practice and explores future directions, including sustainability and ethical implications, to leave readers completely up to date. Based on the previous bestseller, Genetic Improvement of Cattle and Sheep, this book has been completely revised, expanded and redesigned to be an essential textbook for undergraduate, masters and other early postgraduate-level students in agriculture, animal and veterinary science, as well as breeders, farmers, industry technical staff, advisors and extension workers.